Selective and Wash-Resistant Fluorescent Dihydrocodeinone Derivatives Allow Single-Molecule Imaging of mu-Opioid Receptor Dimerization - Gentzsch, Christian; Seier, Kerstin; Drakopoulos, Antonios; Jobin, Marie-Lise; Lanoiselee, Yann; Koszegi, Zsombor; Maurel, Damien; Sounier, Remy; Hübner, Harald; Gmeiner, Peter; Granier, Sebastien; Calebiro, Davide; et al. (Angewandte Chemie International Edition, 2020)
mu-Opioid receptors (mu-ORs) play a critical role in the modulation of pain and mediate the effects of the most powerful analgesic drugs. Despite extensive efforts, it remains insufficiently understood how mu-ORs produce specific effects in living cells. We developed new fluorescent ligands based on the mu-OR antagonist E-p-nitrocinnamoylamino-dihydrocodeinone (CACO), that display high affinity, long residence time and pronounced selectivity. Using these ligands, we achieved single-molecule imaging of mu-ORs on the surface of living cells at physiological expression levels. Our results reveal a high heterogeneity in the diffusion of mu-ORs, with a relevant immobile fraction. Using a pair of fluorescent ligands of different color, we provide evidence that mu-ORs interact with each other to form short-lived homodimers on the plasma membrane. This approach provides a new strategy to investigate mu-OR pharmacology at single-molecule level.
CRIS-Team WoS Importer:2020-01-17